Excited state structural analysis for correlated many-electron systems - Luzanov, A.V. (Functional Materials, 2014)
The excited states structural analysis (ESSA) which was previously developed by the author and coll. (1980, 2010) is extended to a typical equation-of-motion approach within the coupled cluster theory. The extended ESSA allows one to interpret highly correlated excited states, particularly those which occur in molecular singlet fission processes and related optoelectronic devices.